2021
DOI: 10.1002/app.51268
|View full text |Cite
|
Sign up to set email alerts
|

High‐temperature resistant polyimide‐based sandwich‐structured dielectric nanocomposite films with enhanced energy density and efficiency

Abstract: Development of advanced dielectric materials with both high‐electric energy density and high‐temperature resistant attributes is highly desirable in modern electronics and electrical systems. Herein, a series of polyimide (PI)‐based sandwich‐structured dielectric nanocomposite films have been attempted to develop the advanced high‐temperature resistant capacitor films, wherein the boron nitride nanosheets/PI nanocomposite acts as the outer layers and the zinc oxide (ZnO)/PI as the middle layer. Benefitting fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Figure b shows the FTIR spectra of the films. The characteristic imide absorption peaks of asymmetrical and symmetrical CO stretching, C–N stretching, and CO bending of the imide ring were observed at 1777.44, 1717.16 cm –1 , and 1368.54 and 719.49 cm –1 in all of the films. , And the characteristic peaks of aluminum (432.80, 564.17 cm –1 , α-Al 2 O 3 ) become more pronounced as the volume ratio of alumina increases. , And the content of 1DTiO 2 was low and failed to show the characteristic peak. Figure c shows the T g of all films at around 320 °C, indicating that the addition of alumina and titanium dioxide does not affect the structure of the PI itself.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Figure b shows the FTIR spectra of the films. The characteristic imide absorption peaks of asymmetrical and symmetrical CO stretching, C–N stretching, and CO bending of the imide ring were observed at 1777.44, 1717.16 cm –1 , and 1368.54 and 719.49 cm –1 in all of the films. , And the characteristic peaks of aluminum (432.80, 564.17 cm –1 , α-Al 2 O 3 ) become more pronounced as the volume ratio of alumina increases. , And the content of 1DTiO 2 was low and failed to show the characteristic peak. Figure c shows the T g of all films at around 320 °C, indicating that the addition of alumina and titanium dioxide does not affect the structure of the PI itself.…”
Section: Resultsmentioning
confidence: 96%
“…The characteristic imide absorption peaks of asymmetrical and symmetrical C�O stretching, C−N stretching, and C�O bending of the imide ring were observed at 1777.44, 1717.16 cm −1 , and 1368.54 and 719.49 cm −1 in all of the films. 26,27 And the characteristic peaks of aluminum (432.80, 564.17 cm −1 , α-Al 2 O 3 ) become more pronounced as the volume ratio of alumina increases. 28,29 And the content of 1DTiO 2 was low and failed to show the characteristic peak.…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…Figure a illustrates the comparison of U e and η of PI/BNNS film with reported PI dielectric materials, including intrinsic PI, , PI nanocomposites, all-organic PI composites, ,, multilayer-structured PI composites, , and PI composites containing inorganic layer. ,, The blue, gray, yellow, purple, and green boxes are used to classify the above materials on the right of Figure a. It is found that the PI/BNNS film achieves the maximum U e when η is greater than 90%, which is far superior to the reported PI-based dielectric materials at different temperatures.…”
Section: Resultsmentioning
confidence: 98%
“…The introduction of inorganic fillers into the multilayered structure can further increase the corresponding functional properties, either polarization or insulation, which gives the polymer composite dielectric more microstructure design degrees of freedom. [182][183][184][185] Past state-of-the-art literature has reported that incorporating inorganic fillers with different ε r into the polymer matrix would significantly enhance their polarization or insulation, but the distortion of electric fields will appear in the polymer dielectrics no matter what inorganic filler is chosen because of the difference between the matrix and the filler. This makes the E b of the polymer dielectric decline rapidly.…”
Section: Multilayered Polymer Composite Dielectricsmentioning
confidence: 99%